2015
DOI: 10.3233/thc-150952
|View full text |Cite
|
Sign up to set email alerts
|

Impact-induced soft-tissue vibrations associate with muscle activation in human landing movements: An accelerometry and EMG evaluation

Abstract: Abstract. BACKGROUND:Previous studies have not used neurophysiological methodology to explore the damping effects on induced soft-tissue vibrations and muscle responses. OBJECTIVE: This study aimed to investigate the changes in activation of the musculoskeletal system in response to soft-tissue vibrations with different applied compression conditions in a drop-jump landing task. METHODS: Twelve trained male participants were instructed to perform drop-jump landings in compression shorts (CS) and regular shorts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Inconsistent with the aforementioned findings, Moon et al (2016) reported that leg compression reduced the activation of the rectus femoris in isokinetic tests but had no significant effect on knee extension strength. However, direct comparisons of the findings between these two studies are not appropriate due to the different types of exercise (continuous passive vibrations vs. isokinetic leg extension/flexion) and external pressures adopted (0, 20, and 40 mmHg vs. 0, 9, and 18% compression) Fu et al (2012 , 2015) conducted a series of research on leg compression by testing different muscle contractions (i.e., isometric, isokinetic, and isotonic) and muscle activations for athletes. Their results showed that, while compression shorts did not affect muscle strength acutely, it did reduce the EMG activities and maintained similar power output during repetitive muscle contractions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inconsistent with the aforementioned findings, Moon et al (2016) reported that leg compression reduced the activation of the rectus femoris in isokinetic tests but had no significant effect on knee extension strength. However, direct comparisons of the findings between these two studies are not appropriate due to the different types of exercise (continuous passive vibrations vs. isokinetic leg extension/flexion) and external pressures adopted (0, 20, and 40 mmHg vs. 0, 9, and 18% compression) Fu et al (2012 , 2015) conducted a series of research on leg compression by testing different muscle contractions (i.e., isometric, isokinetic, and isotonic) and muscle activations for athletes. Their results showed that, while compression shorts did not affect muscle strength acutely, it did reduce the EMG activities and maintained similar power output during repetitive muscle contractions.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the relevance of the physiology and biomechanics in fatigue and recovery remains unclear. CGs reduce muscle vibration and activation without affecting performance ( Fu et al, 2012 , 2015 ; Broatch et al, 2019 ). Researchers suggested that, for forms of movements that require frequent and repetitive muscle contractions, reduced muscle activation can improve contraction efficiency and decrease energy loss and muscle fatigue.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible to compute damping from a temporal analysis (e.g. model or logarithm decrement between peaks) [ 20 , 39 ]. However, other methods [ 40 , 41 ] are preferred to compute frequency and damping of the vibration signal in running.…”
Section: Origin and Characteristics Of Soft Tissue Vibrations In Runningmentioning
confidence: 99%
“…The impact load is two to three times of the body weight at touchdown, which is considered to be the main risk factor for causing damage such as stress fracture/fracture, patellofemoral joint pain syndrome, and plantar fasciitis [2][3][4][5]. Thus, how to reduce the impact and risk of running injury has always been a hot issue in the biomechanics, sports medicine, rehabilitation, and related industries [6,7].…”
Section: Introductionmentioning
confidence: 99%